2018
DOI: 10.1177/0300060518785543
|View full text |Cite
|
Sign up to set email alerts
|

Acute allograft rejection in liver transplant recipients: Incidence, risk factors, treatment success, and impact on graft failure

Abstract: ObjectiveThis study was performed to identify risk factors for acute cellular rejection after liver transplantation (LT).MethodsConsecutive LT recipients who underwent surgery in our institution from 2002 to 2015 were retrospectively evaluated.ResultsIn total, 176 patients were eligible for statistical analysis. During a mean observation period of 61.1 ± 36.3 months, 43 episodes of acute rejection were evident. Of these, 34 (79.0%) were responsive to methylprednisolone, 3 (7.0%) were treated by adjusting the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
(57 reference statements)
2
45
1
1
Order By: Relevance
“…Despite the great advances made in immunosuppression (IS) in the past decades, the incidence of acute cellular rejection (ACR) after liver transplantation (LT) is still approximately 21%‐27% . In addition, IS therapy has significant adverse effects, including an increased risk of opportunistic infections, particularly during the first months following transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the great advances made in immunosuppression (IS) in the past decades, the incidence of acute cellular rejection (ACR) after liver transplantation (LT) is still approximately 21%‐27% . In addition, IS therapy has significant adverse effects, including an increased risk of opportunistic infections, particularly during the first months following transplantation.…”
mentioning
confidence: 99%
“…approximately 21%-27%. (1,2) In addition, IS therapy has significant adverse effects, including an increased risk of opportunistic infections, particularly during the first months following transplantation. Currently, the state of IS is evaluated using immunosuppressant levels as a surrogate marker.…”
mentioning
confidence: 99%
“…It is further thought that T-memory cells that are generated in an inflammatory environment act as a barrier to tolerance induction. (10) This explanation gives credence to the observation of increasing ACR related to longer CITs (8,(15)(16)(17)(18) and biliary complications,(9) which are known to cause inflammation. Our data illustrates the increased risk of ACR with longer CIT; however, the expected increased risk of ACR was not shown in those patients with biliary complications.…”
Section: Discussionmentioning
confidence: 60%
“…The risk of ACR is thought to be highest in the early post-transplant period, and this risk declines over time with development of tolerance for the liver allograft. (10) In published studies, the incidence of ACR is reported between 7% (11) and 20%, (8,12) and even up to half of all recipients (3,4,13) although the time period over which 'acute rejection' can be diagnosed varies between studies, ranging between 3 (3,12,14) and 12 months. (11) The incidence of ACR of 22% in our cohort at 3 months is in keeping with extant literature, and on par with international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cellular rejection is a common complication after liver transplantation that occurs in about 20% to 40% liver transplant recipients. 1,2 It has been described that donor dendritic cells (DCs) as antigen-presenting cells are the main instigators of acute cellular liver transplant rejection due to their potent capacity to stimulate recipient T-cell responses against the graft. 3 DCs express the lymphoid-specific protein tyrosine phosphatase (Lyp) encoded by PTPN22 gene located on chromosome 1p13.3-13.1.…”
mentioning
confidence: 99%